Decision support tools for sustainable water management: Lessons learned from two decades of using MULINO-DSS - Carlo Giupponi; Panagiotis Balabanis; George Cojocaru; Jacobo F. Vázquez; Jaroslav Mysiak (Cambridge Prisms: Water, 2024)
In late 2000, the European Union adopted the Water Framework Directive (WFD) and funded a series of research and innovation projects to support its implementation. One of these was the MULINO project (MULti-sectoral, INtegrated and Operational Decision Support System for Sustainable Use of Water Resources at the Catchment Scale). Its main product was a decision support system (mDSS) tool designed to help water managers make choices related to WFD implementation in a participatory manner. After the end of MULINO, a long sequence of research projects allowed for the maintenance and continuous development of its tool, which has been applied for more than 20 years in various contexts related to environmental and integrated management. This experience and an analysis of the literature allow us to draw some general conclusions regarding DSS tools for water management and their role in our societies. Lessons learned are proposed, from the need to frame tools within sound methodological frameworks for the management of decision processes, supporting instead of substituting decision-makers in their roles, to the trade-offs that appear between ease of use and specificity on one side and flexibility and reusability on the other. The specific strengths attributed to mDSS include the provision of an interface based on a simplified and understandable conceptual framework that facilitates communication with interested parties, the flexibility and ability to approach a wide variety of decisional issues, the relatively simple and understandable decision rules provided by the tool, and the simplified connections with other software environments. This paper presents the current version of the software and reports on the experience of its development and use over more than two decades; it also identifies the way forward.